CD3+CD56+ natural killer T cell infiltration is increased in cervical cancer and negatively correlated with tumour progression. Issue 1 (1st January 2019) - Tu, Yunxia; Pan, Mei; Song, Shuhong; Hua, Jinren; Liu, Rongfang; Li, Longyu
Abstract: This study investigated the phenotype and function of natural killer T (NKT) cells infiltrating cervical cancer tissues, in an attempt to understand the regulation of NKT cells by cervical cancer cells. Forty-two patients with cervical cancer were included. Flow cytometry was used to analyze the percentage of NKT cells in tumour tissues and its correlation with clinical staging and lymphatic metastasis. The expression of surface receptor and effector molecules on infiltrating NKT cells was determined. The changes of the phenotype, subtype and cytotoxicity of NKT cells were investigated. The regulation of NKT cells by cervical cancer cells was investigated by co-culture with HeLa or SiHa cells. The effect of TGF-β1 on NKT activity regulated by cervical cancer cells was studied. The results showed that the infiltration of NKT cells in cervical cancer tissues was significantly higher than that in tumour-adjacent tissues, and the degree of infiltration was negatively correlated with the progression of the disease. The activity and killing effect of infiltrating NKT were inhibited in cervical cancer tissues, leading to increase of CD4 + NKT cells and decrease of CD8 − CD4 − NKT cells. The activity of NKT cells was down-regulated by co-culture with cervical cancer cells, but subtypes of NKT cells were not altered. Cervical cancer cells inhibited the function of NKT cells by secreting TGF-β1. The study demonstrates that the infiltration of NKT cells in cervical cancer tissues is increased significantly and negatively correlated with tumour progression.